PENTINGNYA MORALITAS SEBAGAI LANDASAN DALAM PENDIDIKAN - Putu Sanjaya (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
A moral educator is one of the prerequisites for implementing education. Educatorswho have good morals will be able to carry out their duties and obligations well in providingeducation to their students. Educators are responsible for passing on the values and norms tothe next generation so that a value conservation process occurs because through the educationalprocess efforts are made to create new values. Teachers as educators and human elements ineducation must uphold the rules in behaving (immoral) so that they are always within theprevailing norms so that the expectations of students to imitate good deeds and good behaviorcan also be implemented.